2010
DOI: 10.33549/physiolres.931708
|View full text |Cite
|
Sign up to set email alerts
|

Fitting a Single-Phase Model to the Post-Exercise Changes in Heart Rate and Oxygen Uptake

Abstract: The kinetics of post-exercise heart rate (HR) and oxygen consumption (EPOC) was studied in 10 elite cyclists subjected to four laboratory cycle ergometer maximal exercises lasting 30, 90, 180 or 360 s. Heart rate and oxygen uptake (VO2) were recorded over a period of 6 min after the exercise. By applying the logit transformation to the recorded variables and relating them to the decimal logarithm of the recovery time, uniform single-phase courses of changes were shown for both variables in all subjects and exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…One could infer, therefore, that VO 2 did not fall as quickly as HR between raking efforts which in turn did not reduce mean VO 2 below the level observed in continuous raking tasks. Whilst this hypothesis could not be tested using the current data, such a conclusion would contradict work in the excess post-exercise oxygen consumption area where authors have shown that VO 2 recovers to baseline levels more quickly than HR [32,33]. More work examining the frequency and duration of fireground tasks and the impact these variables have on the physiological response across and between task repetitions is required before definitive conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 62%
“…One could infer, therefore, that VO 2 did not fall as quickly as HR between raking efforts which in turn did not reduce mean VO 2 below the level observed in continuous raking tasks. Whilst this hypothesis could not be tested using the current data, such a conclusion would contradict work in the excess post-exercise oxygen consumption area where authors have shown that VO 2 recovers to baseline levels more quickly than HR [32,33]. More work examining the frequency and duration of fireground tasks and the impact these variables have on the physiological response across and between task repetitions is required before definitive conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 62%
“…Hormon, enzim ve nöromusküler kavşaktaki kimyasallarda da yetersizlik baş gösterir. 12,13 Sporcunun bu yıkımlar sonucu yeterince toparlanamadan bir sonraki antrenmana çıkması per-formansını olumsuz etkileyecektir. 9 Toparlanma sürecinde organizmada meydana gelen bu yıkımlar iyileştirilmeye çalışılır.…”
Section: Discussionunclassified
“…Sporcu, mental olarak da yüklenmenin verdiği psikolojik yükü üstünden atmaya çalışmaktadır. 12 Bu süreç; antrenmanın şiddeti, kapsamı, sporcunun form durumu, beslenme vb. faktörlere bağlı olarak uzun zaman alabilmektedir.…”
Section: Discussionunclassified
“…Kinematics were quantified from 20 running run cycles (10 cycles before and after the respective specific physiological event) at 5 different timepoints. The timepoints corresponded to previously published VO 2 measures (explained in Walsh et al, 2015, 2017) and were: (1) the start of the 10th minute of the control run (CR steady state, or CR SS ), (2) 30 s after reaching the pre-cycle CR self-selected speed (TR 30 ), (3) theoretical “half-time” to steady state VO 2 calculated using a remodelled logarithm ( 20 ), TR t1/2 , (4) mean response time (TR MRT ) defined as the time required to reach about 63% of steady state ( 21 ), and (5) at the beginning of the 3rd minute when running after cycling [steady state or TR SS , ( 4 )]. Run cycles were defined using visual inspection of the kinematics of running as the period between heel strike to ipsilateral heel strike (0%–100%), that were determined by identifying the point of heel strike to toe-off of the right foot ( 22 ).…”
Section: Methodsmentioning
confidence: 99%